Inovasi Model Pembiayaan Digital Pada Lembaga Keuangan Mikro Syariah Untuk Meningkatkan Inklusi Keuangan Komunitas Marginal - Khandi Tungga Wijaya; Andriani Samsuri (Universitas Mataram, 2025)
This study aims to analyze the innovation of digital financing models in Islamic Microfinance Institutions (IMFIs) as a strategy to enhance financial inclusion among marginalized communities in Indonesia. The research is motivated by the financial access gap among low-income groups. The study employs a Systematic Literature Review (SLR) approach by reviewing national and international journal articles published between 2019 and 2025 that are relevant to the topics of digitalization, Islamic microfinance, and financial inclusion. The review process involved systematic stages of literature collection, selection, and thematic analysis to identify patterns, trends, and research gaps. The findings reveal that digital innovations such as mobile banking, Islamic peer-to-peer lending, social crowdfunding, and online information systems enhance institutional efficiency, transparency, and access to financial services for low-income groups. Moreover, digitalization strengthens financial literacy and economic empowerment for marginalized communities. However, key challenges remain, including low digital literacy, infrastructure limitations, and institutional readiness.